Timing And Sequencing Of Orthognathic Procedures In Adolescent Patients: A Systematic Review - Agarwal, Vivek; Mishra, Mayukh; Jana, Debapratim; Samanta, Jaydeep; Maity, Chirantan; Banerjee, Anirban (Journal of Neonatal Surgery, 2025)
Orthognathic surgery in adolescent patients aims to correct severe dentofacial deformities and improve both function and aesthetics. The timing and sequencing of these procedures are critical factors that influence the outcome and long-term stability. Early intervention may be beneficial for skeletal maturity and long-term results, though careful consideration of the patient's growth potential is crucial. This systematic review examines existing literature on the timing and sequencing of orthognathic procedures in adolescent patients, with a focus on the appropriate age for surgery, the sequence of surgical intervention, and the impact on facial growth and development. The review also addresses the impact of different surgical sequences, such as maxilla-first or mandible-first approaches, and highlights the role of orthodontic preparation in achieving optimal outcomes. Based on the analysis, the review provides recommendations for clinicians on how to time and sequence orthognathic procedures to achieve the best functional and aesthetic results for adolescent patients.